Nanopartículas lipídicas sólidas magnéticas multifuncionais à base de cera de carnaúba com potencial aplicação teragnóstica - Moura, Carolina de Lima e (2017)
The nanostructured magnetic materials, made up of iron oxides, are already used in procedures for the diagnosis and treatment of patients. Among the uses are the diagnosis by nuclear magnetic resonance, treatment by magnetic hyperthermia and bioactive loading. Magnetic nanosystems can be used in the treatment of magnetic hyperthermia even without the incorporation of the drug, since the fight against the tumor is done by increasing the temperature in the place, an increase of 5 ºC above the body temperature is sufficient to kill a tumor without affecting the Neighboring cells. A melt-emulsification procedure was performed to formulate solid lipid nanoparticle (SLN) and magnetic solid lipid nanoparticle (MSLN) based on carnauba wax and Fe3O4@AO in different concentrations. Through the dynamic light scattering (DLS) it was possible to obtain the average particle size ranging from 150.77 to 182.17 nm and the zeta potential that reached very negative values -53.35 to -59.75 mV, high physical stability of the system. The incorporation of iron oxide by the solid lipid matrix, Preferably in the nucleus of the nanoparticles, was observed through the micrographies of the Transmission Electron Microscopy (TEM). The images of TEM and Scanning Electron Microscopy (SEM) allowed analyzing the material morphologically, revealing a spherical shape acquired by the SLN and MSLNs. In the Magnetic Hyperthermia (HM) test as NLSMs 3%, 5% and 7% generated a satisfactory temperature increase, since, in 10 minutes in the systems driven by an increase of 7.59, 9.18 and 13.4 ° C, respectively. It was observed that the release of the drug by HM showed better results than the method without application of the magnetic field. The transverse relaxation rate of SLNMs for a 3T field was 864.18 to 930.35 mM (Fe)-1s-1, which clearly translates into a dark contrast agent for use in magnetic resonance imaging (MRI). It should be noted that the MSLN 7% translates a darker image than the other MSLNs, due to its higher concentration of iron oxide. The MSLNs showed potential application in magnetic hyperthermia and MRI. The results are quite promising for development for therapeutic purposes.